Key health promotion factors among male members of staff at a higher educational institution: A cross-sectional postal survey - Reid Garth; van Teijlingen Edwin R; Vasianovich Alena; Scott Neil W (BMC, 2008)
Abstract Background Men's lifestyles are generally less healthy than women's. This study identifies associations between health-related behaviour in different groups of men working in a Higher Education (HE) institution. In addition, men were asked whether they regarded their health-related behaviours as a concern. This article highlights smoking, consumption of alcohol and physical activity as most common men's health-related lifestyle behaviours. Methods A descriptive cross-sectional survey was conducted among all male staff employed by a Higher Education institute in Scotland using a postal self-completed questionnaire. A total of 1,335 questionnaires were distributed and 501 were returned completed (38% return rate). The data were analysed using SPSS 13.0 for Windows. Results Less than 10% currently smoked and almost 44% of these smokers were light smokers. Marital status, job title, consumption of alcohol and physical activity level were the major factors associated with smoking behaviour. Men in manual jobs were far more likely to smoke. Nearly all (90%) consumed alcohol, and almost 37% had more than recommended eight units of alcohol per day at least once a week and 16% had more than 21 units weekly. Younger men reported higher amount of units of alcohol on their heaviest day and per week. Approximately 80% were physically active, but less than 40% met the current Government guidelines for moderate physical activity. Most men wanted to increase their activity level. Conclusion There are areas of health-related behaviour, which should be addressed in populations of this kind. Needs assessment could indicate which public health interventions would be most appropriately aimed at this target group. However, the low response rate calls for some caution in interpreting our findings.